2016
DOI: 10.1016/j.socscimed.2016.01.036
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peers on HIV infection expectations among Malawian adolescents: Using an instrumental variables/school fixed effect approach

Abstract: Malawian adolescents overestimate their HIV infection risk. Understanding why they do so is important since such overestimation is likely to be linked to later-life outcomes. This study focuses on the influence peers have on HIV infection expectations. I use novel school-based survey data collected in Malawi between October 2011 and March 2012 (n = 7,910), which has more reliable measures of peers' HIV infection expectations than other studies. I employ a combined instrumental variables/fixed effects methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The respondents each spoke of several experiences in which they were aware of negative self-judgments including disclosure of their HIV status and dating with interpersonal relationships of paramount importance to this age group. As young adults, peer acceptance is extremely important for support and determining self-worth [ 38 ]. It is an age where young people are trying to find their individuality, yet also desire community acceptance [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The respondents each spoke of several experiences in which they were aware of negative self-judgments including disclosure of their HIV status and dating with interpersonal relationships of paramount importance to this age group. As young adults, peer acceptance is extremely important for support and determining self-worth [ 38 ]. It is an age where young people are trying to find their individuality, yet also desire community acceptance [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…As young adults, peer acceptance is extremely important for support and determining self-worth [ 38 ]. It is an age where young people are trying to find their individuality, yet also desire community acceptance [ 38 ]. Study respondents reported that living with HIV created a tension between the need to be themselves while also maintaining social and community acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Active engagement of peers in the design and delivery of HIV services has also been promoted globally in recent years [ 1 , 26 ]. Yet, the evidence supporting the beneficial role of peers in the continuum of the HIV services is limited and is sometimes controversial [ 5 , 28 30 ]. In the RCP, the involvement of adolescents and youth in the design and delivery of linkage-to-care services established an ongoing dialogue between the local healthcare workers and their adolescent and youth clients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, focus is also put on individual gambling participation, entrepreneurial behavior, and donation behavior (Goldberg et al, 2014, Monson et al, 2018, Drouvelis&Marx, 2020) [29][30][31] . In addition, the impact of neighborhood effects on individual wrong behaviors results in suggestions on negative behaviors -reducing individual crime rate and illegal decisions of companies through social multipliers (Kim, 2016,Berg&Nelson, 2016, Gerlinger&Hipp, 2020) [32][33][34] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are several challenges associated with identifying the neighborhood effects. Above all, it is di cult to de ne an appropriate 'neighbor group' (Chen, Jin, and Yue 2010; Kim 2016) [49]; [32] . Besides, the identi cation of neighborhood effects also faces three common concerns (Manski 2013; Ate , & Pourmasoudi, 2019) [50][51] : (1) The contextual effect, which means that the behavior of an individual varies with the exogenous characteristics of the neighbors.…”
Section: The Identi Cation Of Neighborhood Effectsmentioning
confidence: 99%